ANALISIS IMPLEMENTASI STRATEGI PEMASARAN PRODUK PERUMAHAN PANAM PERMATA RESIDENCE PADA PT. HARI SEJAHTERA ABADI - Muammar Rafsyantani; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted at PT Hari Sejahtera Abadi , located on Jl. SM Amin ( Ring Road ) No. 102, Arengka 2 . Pekanbaru . The purpose of this research is to analyze the marketing strategy of housing products panam permata residence at PT. Hari Sejahtera Abadi.In this study, the methodology used is descriptive qualitative approach . Where the sample used is the consumer PT . Hari Sejahtera Abadi. And as a source of information is the leadership and employees of PT. Hari Sejahtera Abadi as policy makers. To determine the sample size using the formula Slovin. Purposive sampling method with sampling, data collection techniques through interviews, questionnaires.From these results it can be seen that the implementation of the marketing strategy implemented by PT. Hari Sejahtera Abadi is pretty good, it's just a promotion strategy should be maximized. Because the results of the study showed that promotional strategies implemented by PT . Hari Sejahtera Abadi located in the unfavorable category.Keywords : Marketing Strategy, Marketing Mix, Product, Price, Promotion, Distribution.